A Philosophical Analysis of the Pusaka Inheritance Distribution Tradition in Kinali District, West Pasaman Regency - Mira Tus Sholikah (QURU’: Journal of Family Law and Culture, 2023)
The existence of inheritance law in West Pasaman cannot be separated from the customary elements that influence it. Traditions or customs in West Pasaman cannot be separated from the philosophy of Adat Basandi Syarak, Syarak Basandi Kitabullah. Seeing the phenomenon that occurs in the field, the author is interested in uncovering the nature of why inheritance in the West Pasaman area focuses more on the female line and what are the factors behind it. The method used in this research is descriptive-qualitative method which is focused on the problem on the basis of facts carried out by means of observation/observation, interviews, and studying documents. This research uses a legal philosophy approach that reveals three aspects, namely ontology, epistimology and axiology. The conclusion of this research is basically in the distribution of inherited property from the ontological aspect, namely the nature of inheritance of Minangkabau customary property originating from customary law originating from the tribe which is then passed down from generation to generation according to the mother's lineage, from the epistemological aspect, namely the origin of the inheritance property comes from Niniak Mamak Datuak Manaruko, from the axiological aspect, namely the aspect of its usefulness to ensure the life of the female party so that her life is not difficult in the future.